Male bodies, objectification and masculinities: A case study on Cyprus - Michael, Artemis (2020)
This dissertation used a qualitative approach for exploring Cypriot male and female reactions on idealised bodies and male objectification. The dissertation reviews themes such as stereotypical presentations and somatotypes as well as introduces masculinities that have been identified throughout the literature. The purpose of this dissertation was to discover if Cypriot male and female participants understand male objectification in advertisements, how they interpret and interact with such advertisements, their thoughts, perceptions and behaviours towards it as well as their feelings. Furthermore, this study wanted to investigate how these individuals determine idealised bodies in advertisements and if education was a pivotal determinant for objectification understanding, thoughts and criticisms through in-depth interviews. The implementation of thematic analysis surfaced 7 themes that were present throughout the interviews including: Rejecting Effectiveness, Bodies, Masculinities and Femininity, Society, Objectification, Homophobia and Industry Problems. After conducting ten in-depth interviews with five Cypriot male and five Cypriot female participants aged 18-29, results indicated that education was not a determining factor, as individuals with higher education were both able and not able to determine objectification. Additionally, idealistic bodies in advertisements were consistently characterised as unrealistic, not reflective of reality and extreme, whereas bodies that are somewhat muscular were characterised as ideal for this specific sample.